Rhein Suppresses Lung Inflammatory Injury Induced by Human Respiratory Syncytial Virus Through Inhibiting NLRP3 Inflammasome Activation via NF-κB Pathway in Mice - Shen, Cunsi; Zhang, Zhengguang; Xie, Tong; Ji, Jianjian; Xu, Jianya; Lin, Lili; Yan, Jing; Kang, An; Dai, Qigang; Dong, Yingmei; Shan, Jinjun; Wang, Shouchuan; et al. (Frontiers in Pharmacology, 2020)
Rhein is one of active anthraquinone components in traditional Chinese herbal medicine Rheum palmatum L., which possess anti-inflammatory, antioxidant, antitumor, antiviral, and hepatoprotective activities. Human respiratory syncytial virus (RSV), a common virus, is able to result in pneumonia and bronchitis. It usually can be seen in infants. However, so far the effects of Rhein on RSV-induced pneumonia are still unknown. As the inflammasome pathway is activated excessively, it is able to lead to inflammatory response and tissue injury in most viral infection process (including RSV infection) of respiratory tract. Therefore, we designed experiments to reveal whether Rhein can treat RSV-induced pneumonia by inhibiting inflammasome pathway. In the present research, we established the pneumonia model of BALB/C mice caused by RSV. First of all, the pathology of lung tissue and the weight of mice were evaluated and the corresponding lung index was calculated. Additionally, the expression of inflammatory genes and proteins and related proteins (NLRP3, ASC and Caspase-1) of NLRP3 inflammasome pathway were detected by Enzyme-linked immunosorbent assay (ELISA), Real-time PCR (RT-PCR), Immuneohistochemistry (IHC), and Western blot (WB). The determination of lung index and lung tissue pathological evaluation revealed that Rhein was able to alleviate lung infection and injury caused by RSV. The results of ELISA showed that Rhein was able to reduce the release of pro-inflammatory cytokines in the serum of RSV-induced BALB/c mice, including IL-1β, IL-6, TNF-α, IL-18, IL-33, etc. Additionally, it was revealed by RT-PCR, IHC, and WB results that Rhein inhibited the immune inflammatory response of RSV-infected mice, which was likely to be associated with the inhibition the related proteins of NLRP3 inflammasome pathway on the mRNA and protein levels, respectively. To sum up, our results indicated that Rhein may inhibit RSV-induced pulmonary inflammatory response effectively; meanwhile, it is emphasized that Rhein therapy is likely to be a promising treatment on the RSV-infected lung inflammation and avoidance of lung tissue damage.